Employability As A Complex Problem - Hernández Corredor, Luisa Fernanda; Beltrán Martínez, Ronald Sneyder (Ingeniería Solidaria, 2020)
Introduction:This article is developed within the framework of the Emple-ap project, coordinated since 2018 by the Universidad Distrital Francisco José de Caldas in Bogotá. Problem:Recent graduates of higher education face a problem of employability that is affected by multiple interdependent and changing variables, actors and contexts, which makes it more complex in nature. However, the problem is usually approached from a simplistic perspective that prevents the construction of proposals that generate a high impact in practice. Objective: The objective of this research is to generate a proposal to study the problem of employability from the perspective of complex thinking. Methodology:The methodology used is based on a literature review and a panel of experts through structural analysis. Results:The predominance of the simplistic approach in the understanding of employability is made evident, being expressed in a limited set of variables and generally focused on the professional. In addition, the structural analysis makes it possible to highlight the high interdependence existing between the variables that encompass different actors and contexts. Conclusions: It is necessary to redirect the approach from which employability is studied, recognizing that the problem must be tackled globally and is in a state of constant change, in order to generate dynamic solutions that adapt to it. Originality:This research offers a first proposal to understand employability as a complex problem, emphasizing the interdependence of variables. Limitations:The presented results are too recent to make a generalization and although the proposed variables were verified in the panel, they have not yet been validated.